Two Giants, One War : Johnson's and Nixon's Relationships with the Media during the Vietnam War (1964-1972) - Miller, Mandy (My University, 2011)
The Vietnam War was one of America's longest wars, and it was also one of the most complex wars the United States had been involved in. While the battle was waging in Vietnam, people at home were, for the first time, able to see the military in action. Television news was fast becoming one of the nation's leading ways to gather news information, and this created the idea that the press helped lose the war in Vietnam. While the impact of journalism during Vietnam is heavily contested, the viewpoints from Johnson's and Nixon's administrations regarding the press are very clear. Negative relationships between the press and both Johnson and Nixon brought forth the "credibility gap" between the media and the government. The relations between the government and the press during Vietnam would thereafter impact the way wars were reported.
Keywords: Johnson, Lyndon B. (Lyndon Baines), 1908-1973--Relations with the press; Nixon, Richard M. (Richard Milhous), 1913-1994--Relations with the press; Vietnam War, 1961-1975--Mass media and the war; Mass media and war--United States; Vietnam War, 1961-1975--Press coverage